2020
DOI: 10.1038/s41434-020-00192-z
|View full text |Cite
|
Sign up to set email alerts
|

Precise and error-prone CRISPR-directed gene editing activity in human CD34+ cells varies widely among patient samples

Abstract: Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and their associated CRISPR-associated nucleases (Cas) are among the most promising technologies for the treatment of hemoglobinopathies including Sickle Cell Disease (SCD). We are only beginning to identify the molecular variables that influence the specificity and the efficiency of CRISPRdirected gene editing, including the position of the cleavage site and the inherent variability among patient samples selected for CRISPR-directed gene editi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
2
15
0
1
Order By: Relevance
“…While successful single base mutation correction was observed, unintended on-site changes were also found at an alarmingly high rate. We have also confirmed other laboratories initial observations that unintended genetic changes were prevalent after CRISPR-Cas gene editing in CD34 + cells 4 , 8 , 9 .…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…While successful single base mutation correction was observed, unintended on-site changes were also found at an alarmingly high rate. We have also confirmed other laboratories initial observations that unintended genetic changes were prevalent after CRISPR-Cas gene editing in CD34 + cells 4 , 8 , 9 .…”
Section: Introductionsupporting
confidence: 91%
“…The most prominent challenge centers on the diversity of genetic outcomes that have resulted from sophisticated attempts to correct a single base mutation using CRISPR-based gene editing. Our work 2 4 and others 5 7 have revealed that while successful point mutation repair can be achieved, it is almost always associated with a significant amount of imprecise editing, particularly at the targeted sites where the CRISPR-Cas complex was designed to act, i.e., on-site mutagenesis .…”
Section: Introductionmentioning
confidence: 88%
“…This was done for example to knockout PD-1 and CD52 for the different types of cancer by electroporating Cas9 and a sgRNA to edit the cells ex vivo . The results indicated that the clinical applications of CRISPR-Cas9 gene-edited T-cells are generally safe and feasible ( Lu et al, 2020 ; Frangoul et al, 2021 ; Modarai et al, 2021 ). The disruption of erythroid enhancer of the BCL11A gene by CRISPR-Cas9 for the treatment of ß-thalassemia has been observed with serious adverse events.…”
Section: Nuclease-based Genome Engineering Technologiesmentioning
confidence: 99%
“…Można użyć przenośni, że komórka, w której zachodzi taka edycja, zamiast planowanej dzięki HDR i donorowemu DNA poprawy, wpada niejako z deszczu pod rynnę, po włączeniu się NHEJ. Tego typu wady metody CRISPR prowadzą do tego, że systemy edycji powodują dużo niezamierzonych zmian, pomimo wprowadzenia donorowego DNA [17][18][19]. Technika TALEN również korzysta z HDR oraz NHEJ i jest w związku z tym obciążona podobnymi mankamentami (ryc.…”
Section: Metoda Crispr-cas9unclassified